Determinantes do spread banc??rio no Brasil e os impactos do Acordo de Basileia III - Cavalcanti, Felipe de Oliveira (2017)
Bank spread can be considered an indicator of the efficiency of an economy's financial system. High spreads can harm the investment and consumption capacity of businesses and households, and, consequently, the economic growth. Using a dynamic panel, with data from 73 commercial banks operating in Brazil, in the period between the second quarter of 2009 and the second quarter of 2016 (29 quarters), this dissertation sought to identify the factors that explain the high spread practiced by Brazilian banks, focusing in particular on the possible impacts from the implementation of the Basel III Accord that is in progress. As results, were detected a positive and significant relationships of the spread with the following variables: administrative and operating expenses, taxation, net profits of banks, compulsory deposits and unemployment. A significant and negative relation with the SELIC rate and inflation were detected too. In addition, it was found that the new level 1 capital and principal capital requirements related to the implementation of the Basel III Accord in Brazil had a positive impact on the spread.